INOVASI PELAYANAN PUBLIK BERTEMA POSYANDU TERNAK BAGI PETERNAK DESA DANGIANG KABUPATEN LOMBOK UTARA - Sagita, Suci Syafti; Fentika, Fena; Juwita, Kartika; Adekantari, Dyah Rizki; Andika, Muhamad; Hidayat, Rahmad; Dermawan, Muhammad Ari (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2024)
Dangiang Village is one of the villages in Kayanagan District, North Lombok Regency, West Nusa Tenggara which has superior potential in the field of animal husbandry. However, farmers often face challenges in cultivation due to lack of knowledge, awareness of the importance of livestock health management, and innovation in increasing livestock productivity. The purpose of implementing this community service activity was to improve livestock health and productivity in Dangiang Village. The method of implementing the activity used was in the form of discussion and direct practice to provide active health services to livestock. The implementation stage included preparation, socialization and implementation, involving collaboration between UMMAT KKN students, local authorities, and livestock experts. The results of this activities carried out in Dangiang Village, North Lombok Regency with the theme of Livestock Posyandu showed a positive impact on livestock health and community welfare. Therefore, it is important to have regular health interventions for livestock to prevent disease, increase productivity, and educate farmers about proper care practices. Collaboration between UMMAT KKN students, local authorities, and livestock experts reflects the effectiveness of community involvement in overcoming agricultural challenges and promoting sustainable livestock processing practices.